Penerapan Digitalisasi Layanan Publik di DISPORABUDPAR Kab. Nganjuk Dengan Aplikasi “Nganjuk Elok” - Raditya Pratama; Ulfa Emi Rahmawati; Puji Hastuti; Intan Sulistyaningrum Sakkinah; Nina Virgiana; Fadillah Wahyu Nugraha; Amirzan Fikri Prasetyo (Journal of Community Development, 2025)
One of the essential obligations of higher education institutions is to engage in community service. To maximize the impact of these activities, collaborations with potential beneficiaries are crucial. Public service organizations are ideal partners for such endeavors. This community service project focused on enhancing the efficiency and accessibility of services at the DISPORABUDPAR of Nganjuk Regency, located at Jl. Diponegoro No. 29, Mangundikaran, Nganjuk District, East Java. Key challenges identified included manual processing of artist registration renewals, the necessity of in-person visits for advice letters and performance permits, disorganized building rental administration, and public confusion regarding event promotion. To address these issues, a mobile and web-based application named "Nganjuk Elok" was developed. This digital solution aims to encourage community participation in cultural and tourism activities while improving the efficiency of budget and resource management within the DISPORABUDPAR. Ultimately, "Nganjuk Elok" has the potential to contribute to local economic growth by attracting more tourists and fostering the creative sector.